(untitled) (Polifonia, 1995)
ABSTRACT: The present article has the main purpose to analyse the following topics: the begining of "Sebastianism"; to relate some religious doctrines of Middle Age with the "Sebastianism"; to place Portugal as a sacral society; the misterious vanishing of D. Sebastião and the faith in Encoberto; the appearing of troops from Bandarra; Priest Vieira and his lectures of the Sebastianism;the poets from Portugal and the Sebastianism; Fernando Pessoa and his distressing trial to understand Portugal; the rereading that fernando Pessoa does from the Sebastianism; A Mensagem and the Sebastianism; A Mensagem and the Fifth Cultural Empire, included in the book called Mensagem by Fernando Pessoa.